1996
DOI: 10.7326/0003-4819-125-1-199607010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Polymorphism of the Angiotensin I-Converting Enzyme Gene Is Associated with Increased Plasma Angiotensin-Converting Enzyme Activity but Not with Increased Risk for Myocardial Infarction and Coronary Artery Disease

Abstract: In an angiographically defined study sample, ACE I/D gene polymorphism was not associated with an increased risk for coronary artery disease or myocardial infarction, despite its effects on plasma ACE activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 0 publications
5
33
0
Order By: Relevance
“…2,19 Other factors also influence the ACE level and these include exercise, diet and body weight. 4,20,21 Elevated ACE levels have been implicated in the pathogenesis of several disorders, 7,8,[19][20][21][22][23] though there are some contradictory reports. 7 In addition, the renin-angiotensin system is known to play an important role in metabolism and influence insulin action, thus affecting different metabolic pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 Other factors also influence the ACE level and these include exercise, diet and body weight. 4,20,21 Elevated ACE levels have been implicated in the pathogenesis of several disorders, 7,8,[19][20][21][22][23] though there are some contradictory reports. 7 In addition, the renin-angiotensin system is known to play an important role in metabolism and influence insulin action, thus affecting different metabolic pathways.…”
mentioning
confidence: 99%
“…2,6,7 In addition, the activity of the renin-angiotensin system appears to be regulated by food intake, suggesting that it may be involved in development of obesity and obesity related hypertension. 4 The genotype of ACE DD is shown to be linked to different disorders, including obesity, hypertension, diabetes mellitus and renal disease.…”
mentioning
confidence: 99%
“…In our study we expect that the number of survival in both gender will be similar, but as we observed that the deviations (differences between observed and expected), were different. When we compare the survival rate among both gender at age group (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) in 1995 vs. (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87) in 2008, we observed more survival among males comparing to females (p=0.003), this means that the rate of mortality was higher among females, and the rate of survival was higher among males (p=0.003). Indeed, in 2008 we expected to have 86 males alive but we were surprised to find 108 males alive, in contrary we expected to have more females alive (157), but we only found 135 alive at 2008.…”
Section: Follow Upmentioning
confidence: 99%
“…Most studies focused on an insertion/deletion (I/D) polymorphism in intron 16 of the ACE gene as a marker for a functional polymorphism, which has been related to a variation in the plasma level of the enzyme [65], and ACE activity [69,71] in a codominant pattern.…”
Section: Angiotensin Converting Enzyme (Ace)mentioning
confidence: 99%
“…5,7 These findings have been recurrently confirmed by several investigators in populations of various ethnic origins. [8][9][10][11][12][13] Thus, the ACE gene is viewed as a quantitative trait locus (QTL) that modulates circulating ACE levels, and the ACE*I/D dimorphism is a marker that is in linkage disequilibrium with functional variants located in the ACE gene. As transient increase of ACE levels has been reported to occur during adolescence, 4 we sought to determine: 1) whether the ACE*I/D dimorphism tracked with ACE levels in younger individuals as well; 2) how these associations compared to those observed in adults; and 3) what the variance of the phenomenon among both adult and younger subjects was.…”
mentioning
confidence: 99%